Apolipoprotein E-ϵ4 and recurrent genital herpes in individuals co-infected with herpes simplex virus type 2 and HIV. Issue 7 (15th August 2008) - Jayasuriya, A N; Itzhaki, R F; Wozniak, M A; Patel, R; Smit, E J; Noone, R; Gilleran, G; Taylor, S; White, D J
Abstract : Apolipoprotein E (APOE) alleles have been associated with the severity of, or susceptibility to, infection by various microbes. We investigated the potential association between the APOE-ϵ4 allele and the rate of recurrence of genital herpes in patients who were HIV positive and herpes simplex virus type 2 (HSV-2) seropositive. The APOE-ϵ4 allele was significantly associated with recurrent genital ulceration independent of ethnicity, antiretroviral therapy and CD4 count (OR 8.3; 95% CI 2.4 to 28.5). To our knowledge, this is the first published study to demonstrate this association and suggests that APOE-ϵ4 may represent a future prognostic marker for symptomatic recurrence of genital herpes in individuals with HIV.